Joining of metal and non-polar polypropylene composite through a simple functional group seeding layer. (6th January 2023) - Khan, A.S.; Liu, F.; Dong, P.
Abstract: Polypropylene (PP) and its composites are one of the hardest to directly join with metals due to their inherent chemical incompatibility. This paper presents a simple, efficient, and cost-effective method for joining PP composite to aluminum alloy in spot welding configuration by seeding the functional groups via an insert layer of PA6 thin film without requiring surface or material pre-treatment. The resulting joint loading capacity is shown to be sufficiently high to consistently develop failures in PP substrates in lap shear tensile tests away from the bonded area. Joint interface microstructure features are examined in detail. Bonding mechanisms are then described based on the detailed observations obtained in this study. Graphical abstract: Unlabelled Image